Advances in microcellular injection moulding. (November 2020) - Llewelyn, Gethin; Rees, Andrew; Griffiths, Christian A; Scholz, Steffen G.
Injection moulding is a well-established replication process for the cost-effective manufacture of polymer-based components. The process has different applications in fields such as medical, automotive and aerospace. To expand the use of polymers to meet growing consumer demands for increased functionality, advanced injection moulding processes have been developed that modifies the polymer to create microcellular structures. Through the creation of microcellular materials, additional functionality can be gained through polymer component weight and processing energy reduction. Microcellular injection moulding shows high potential in creating innovation green manufacturing platforms. This review article aims to present the significant developments that have been achieved in different aspects of microcellular injection moulding. Aspects covered include core-back, gas counter pressure, variable thermal tool moulding and other advanced technologies. The resulting characteristics of creating microcellular injection moulding components through both plasticising agents and nucleating agents are presented. In addition, the article highlights potential areas for research exploitation. In particular, acoustic and thermal applications, nano-cellular injection moulding parts and developments of more accurate simulations.